Whole-genome analysis of a daptomycin-susceptible enterococcus faecium strain and its daptomycin-resistant variant arising during therapy (2013)
Development of daptomycin (DAP) resistance in Enterococcus faecalis has recently been associated with mutations in genes encoding proteins with two main functions: (i) control of the cell envelope stress response to antibiotics and antimicrobial peptides (LiaFSR system) and (ii) cell membrane phospholipid metabolism (glycerophosphoryl diester phosphodiesterase and cardiolipin synthase [cls]). However, the genetic bases for DAP resistance in Enterococcus faecium are unclear. We performed whole-genome comparative analysis of a clinical strain pair, DAP-susceptible E. faecium S447 and its DAP-resistant derivative R446, which was recovered from a single patient during DAP therapy. By comparative whole-genome sequencing, DAP resistance in R446 was associated with changes in 8 genes. Two of these genes encoded proteins involved in phospholipid metabolism: (i) an R218Q substitution in Cls and (ii) an A292G reversion in a putative cyclopropane fatty acid synthase enzyme. The DAP-resistant derivative R446 also exhibited an S333L substitution in the putative histidine kinase YycG, a member of the YycFG system, which, similar to LiaFSR, has been involved in cell envelope homeostasis and DAP resistance in other Gram-positive cocci. Additional changes identified in E. faecium R446 (DAP resistant) included two putative proteins involved in transport (one for carbohydrate and one for sulfate) and three enzymes predicted to play a role in general metabolism. Exchange of the “susceptible” cls allele from S447 for the “resistant” one belonging to R446 did not affect DAP susceptibility. Our results suggest that, apart from the LiaFSR system, the essential YycFG system is likely to be an important mediator of DAP resistance in some E. faecium strains.